Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1055/a-1552-4449
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Outcomes of COVID-19 Patients with Overweight and Obesity: Turkish Nationwide Cohort Study (TurCObesity)

Abstract: Purpose While obesity is related to more severe outcomes of coronavirus disease 2019 (COVID-19), factors leading to poor prognosis still remain unclear. The present study evaluated the outcomes of COVID-19 patients who were overweight or obese and variables associated with severe disease in a large group of consecutive cases. Methods A nationwide retrospective cohort study was performed using the Turkish National Healthcare Database. Demographic characteristics, laboratory tests, comorbidities, and medications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Several studies have identified the high-risk factors for severe COVID-19, including elderly, hypertension, overweight, diabetes, and cardiovascular disease [ 7 , 8 ], while an important population, people living with HIV (PLWH), is under-studied and should not be ignored. By the end of 2020, about 37.7 million people were reported to be living with HIV globally [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have identified the high-risk factors for severe COVID-19, including elderly, hypertension, overweight, diabetes, and cardiovascular disease [ 7 , 8 ], while an important population, people living with HIV (PLWH), is under-studied and should not be ignored. By the end of 2020, about 37.7 million people were reported to be living with HIV globally [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity leads to chronic inflammation and lowered immunity [ 5 ]. Obesity was found to be associated with a higher intubation/mechanical ventilation rate and increased mortality in COVID-19 patients ( p = 0.002) [ 15 ]. Moreover, obesity is a known risk factor for cardiovascular diseases, hypertension, type 2 diabetes mellitus, respiratory diseases, and some types of cancer [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, in a study of two genetic risk scores for obesity, based on 31 or 68 single nucleotide polymorphisms, no associations were found between the scores and changes in obesity markers, and no significant gene–diet interactions were found [ 73 ]. As mentioned previously, obesity is a major risk factor for COVID infection [ 5 , 15 , 74 ]. In a meta-analysis, 10,233 COVID-19 patients with obesity (33.9%) had higher odds of poor outcomes than better outcomes with a pooled OR of 1.88 (95% CI: 1.25–2.80; p = 0.002) [ 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective cohort study with 14,625 patients in Turkey, Sahin et al observed that hospitalization, ICU admission, intubation/ventilation, lung involvement and mortality were significantly higher in overweight and obese patients. On adjusted analysis, overweight (OR, 95% CI: 1.82, 1.04-3.21; p = 0.037) and obesity (OR, 95% CI: 2.69, 1.02-1.05; p < 0.001) were associated with a higher rate of intubation/mechanical ventilation, but only obesity was associated with increased mortality (OR, 95% CI: 2.56, 1.40-4.67; p = 0.002) (34).…”
Section: Obesity In Patients With Covid-19 and Admission To The Icumentioning
confidence: 97%